Education on Medication Use and Healthy Eating for the Elderly - Sri Nabawiyati Nurul Makiyah; Sri Tasminatun (Jurnal Dunia Kesmas, 2026)
The elderly are a group vulnerable to non-communicable diseases, so they regularly consume medication and experience a decrease in appetite. The aims of this community service activity are checking the blood quality,  socializing the wise use of medicines and good food diet for the elderly. The location of this community service is in Nanggulan hamlet, Sendangagung, Minggir, Sleman DIY. The methods of this community service activity are laboratory checking blood quality and counseling. Evaluation of community service activities with pretest and posttest. The results of the pretest and posttest were analyzed using the t-test. This community service activity was attended by 54 elderly. The results showed that the elderly's blood pressure and cholesterol levels were relatively high. Uric acid levels in elderly men are normal, but in elderly women are high. The elderly's blood glucose levels are normal. The post-test results were significantly higher than the pre-test results (p0.05). It was concluded that there was an increase in the knowledge of the elderly after education was provided about wisely taking medicine and good eating habits for the elderly.